2022
DOI: 10.1093/humrep/deac112
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell senescence contributes to impaired endometrial decidualization and defective interaction with trophoblast cells

Abstract: STUDY QUESTION What are the consequences of endometrial stromal cell (EnSC) senescence for endometrial function? SUMMARY ANSWER Senescence of EnSC contributes to impaired endometrial decidualization and impaired interaction with trophoblast cells but application of senomorphics diminishes the adverse effects of senescent EnSC on decidualization and implantation. WHAT IS KNOWN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 72 publications
0
24
0
2
Order By: Relevance
“…Implantation failure was associated with increased levels of aging hESCs during the proliferative phase of the menstrual cycle [ 44 ]. In addition, a small number of primary cultured hESCs from patients without endometrial lesions scheduled for in vitro fertilization demonstrated a strong correlation between senescence marker levels and inhibition of decidualization, decreased invasive capacity, and implantation failure rates [ 45 ]. IL15 secreted from decidual hESCs activates uNK cells, and activated-uNK cells might eliminate senescent decidual hESCs [ 33 ].…”
Section: Functions Of Decidualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Implantation failure was associated with increased levels of aging hESCs during the proliferative phase of the menstrual cycle [ 44 ]. In addition, a small number of primary cultured hESCs from patients without endometrial lesions scheduled for in vitro fertilization demonstrated a strong correlation between senescence marker levels and inhibition of decidualization, decreased invasive capacity, and implantation failure rates [ 45 ]. IL15 secreted from decidual hESCs activates uNK cells, and activated-uNK cells might eliminate senescent decidual hESCs [ 33 ].…”
Section: Functions Of Decidualizationmentioning
confidence: 99%
“…In the decidualization process, the balance between senescence and differentiation needs to be appropriately maintained, and disruption of this balance may lead to abnormal decidualization [ 34 , 46 ] and subsequent pre-term birth [ 35 , 36 , 47 ]. Senescent hESCs were found to reinforcing dysfunction of the stromal compartment via secretome changes [ 45 ]. Application of senomorphic agents to suppress the senescence phenotype reduced the negative effects on decidualization and implantation of senescent hESCs [ 45 ].…”
Section: Functions Of Decidualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a subpopulation of endometrial stromal cells undergo senescence and secrete endometrial receptivity mediators. 41 Conversely, endometrial decidual cell senescence has been associated with implantation failure 42,43 and recurrent pregnancy loss. 44 cells during postpartum uterine remodeling in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Deryabin et al. uncovered that premature senescence of EnSC could alter the “meta-signature” of human endometrial receptivity and affect embryo invasion based on an in-vitro implantation model ( 52 ). Moreover, studies by Chen et al.…”
Section: Discussionmentioning
confidence: 99%